2017
DOI: 10.1017/s2045796017000166
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular mortality in people with schizophrenia: a 24-year national register study

Abstract: AimsPeople who have schizophrenia die earlier from somatic diseases than do people in the general population, but information about cardiovascular deaths in people who have schizophrenia is limited. We analysed mortality in all age groups of people with schizophrenia by specific cardiovascular diseases (CVDs), focusing on five CVD diagnoses: coronary heart disease, acute myocardial infarction, cerebrovascular disease, heart failure and cardiac arrhythmias. We also compared hospital admissions for CVDs in peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 25 publications
3
88
0
4
Order By: Relevance
“…The high prevalence of overweight and metabolic abnormalities has become a major concern in schizophrenia patients [3][4][5]. This information regarding the effect of highrisk genotypes in relation to gender differences and/ or smoking status may be used to prevent overweight and metabolic abnormalities, although further investigations in larger and more diverse populations are needed to verify these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence of overweight and metabolic abnormalities has become a major concern in schizophrenia patients [3][4][5]. This information regarding the effect of highrisk genotypes in relation to gender differences and/ or smoking status may be used to prevent overweight and metabolic abnormalities, although further investigations in larger and more diverse populations are needed to verify these findings.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic abnormalities in schizophrenia patients are strongly associated with the development of metabolic diseases including type 2 diabetes and cardiovascular diseases in comparison with general populations [3,4]. Schizophrenia patients with metabolic diseases are at an increased risk of poor adherence to treatments, an impaired cognitive function, a short life expectancy and a decline in the quality of life [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many adverse health behaviours that increase risk of cancer, such as smoking, low physical activity and poor diet, are also risk factors for cardiovascular disease—the main cause of premature mortality in people with schizophrenia 4. However, as public health interventions that are effective for reducing unhealthy behaviours in the general population often fail to reach people with schizophrenia,5 research is needed into how to improve and sustain healthy living in this group.…”
Section: What Next In Researchmentioning
confidence: 99%
“…− Such studies have indicated that patients with psychiatric disorders may experience worsening of cardiovascular diseases due to dysfunction of the HPA axis and autonomic nervous system, thereby leading to increased levels of cortisol, blood cholesterol (triglycerides), and blood pressure . Some studies have also indicated that psychiatric disorders are associated with platelet activation and dysregulation of the immunoinflammatory system, increasing the risk of cardio‐ and cerebrovascular diseases.…”
mentioning
confidence: 99%